MODEL TARIKAN GUNA LAHAN PADA JALAN PROBOLINGGO-LUMAJANG (FSTPT Indonesia, 2023)
Development in Probolinggo and Lumajang districts requires infrastructure as a support. The Probolinggo-Lumajang road is a primary collector road infrastructure that connects two regencies, namely Probolinggo Regency and Lumajang Regency. The Probolinggo-Lumajang road has an important role as supporting all access and the course of economic activity in the East Java region. The Probolinggo-Lumajang road is one of the roads that acts as a distribution channel for raw and finished goods from the eastern part of East Java to the western part of East Java. This study aims to create a land use pull model in the sub-districts connected to the Probolinggo-Lumajang area. This study uses an analysis of the land use attraction, interaction analysis of the model of attraction of land use movement, analysis of physical characteristics, and analysis of traffic characteristics. The results showed that the education land use attraction model was influenced by the number of school students and the size of the school building, the trade and service land use attraction model was influenced by building area, parking area, and the number of visitors to trade and services, so that the results of the application of the trip attraction model on each land use result in the movement volume of the land use attraction on the Jl. Probolinggo-Lumajang as many as 3,667 light vehicles/day. ABSTRAK Pengembangan pada Kabupaten Probolinggo dan Kabupaten Lumajang memerlukan infrastruktur sebagai penunjang. Jalan Probolinggo-Lumajang merupakan infrastruktur jalan kolektor primer yang menghubungkan dua kabupaten yaitu Kabupaten Probolinggo dan Kabupaten Lumajang. Jalan Probolinggo-Lumajang memiliki peranan penting sebagai penunjang segala akses dan jalannya aktivitas ekonomi pada wilayah Jawa Timur. Jalan Probolinggo-Lumajang merupakan salah satu jalan yang berperan sebagai jalur distribusi barang mentah maupun barang jadi dari wilayah Jawa Timur bagian timur dengan Jawa Timur bagian barat. Penelitian ini bertujuan untuk membuat model tarikan guna lahan pada kecamatan yang terhubung pada wilayah Probolinggo-Lumajang. Penelitian ini menggunakan analisis tarikan pergerakan guna lahan, analisis interaksi model tarikan pergerakan guna lahan, analisis karakteristik fisik, dan analisis karakteristik lalu lintas. Hasil penelitian menunjukkan bahwa model tarikan guna lahan pendidikan dipengaruhi oleh jumlah siswa dan luas bangunan, model tarikan guna lahan perdagangan dan jasa dipengaruhi oleh luas bangunan, luas parkir, dan jumlah pengunjung, sehingga hasil penerapan model tarikan pada masing-masing guna lahan menghasilkan volume pergerakan dari tarikan guna lahan pada ruas Jl. Probolinggo-Lumajang sebanyak 3.667 SKR/hari.